An Open Framework for Rapid Prototyping of Signal Processing Applications. (8th December 2009) - Pelcat, Maxime; Piat, Jonathan; Wipliez, Matthieu; Aridhi, Slaheddine; Nezan, Jean-François
Abstract : Embedded real-time applications in communication systems have significant timing constraints, thus requiring multiple computation units. Manually exploring the potential parallelism of an application deployed on multicore architectures is greatly time-consuming. This paper presents an open-source Eclipse-based framework which aims to facilitate the exploration and development processes in this context. The framework includes a generic graph editor (Graphiti), a graph transformation library (SDF4J) and an automatic mapper/scheduler tool with simulation and code generation capabilities (PREESM). The input of the framework is composed of a scenario description and two graphs, one graph describes an algorithm and the second graph describes an architecture. The rapid prototyping results of a 3GPP Long-Term Evolution (LTE) algorithm on a multicore digital signal processor illustrate both the features and the capabilities of this framework.